Methodology for Assessing the Level of Digitalization of the Construction Industry - A. S. Mishchenko (Цифровая трансформация)
As part of the study, a methodology was developed to assess the level of digitalization of the construction industry based on an analysis of the specifics of the functioning and process of introducing digital technologies into the work of construction organizations, as well as the existing methodological framework for assessing the level of use of digital technologies in various economic systems offered by international companies. The methodology is based on the current algorithm for introducing digital tools into the work of construction companies, which simultaneously reflects all stages of the life cycle of construction projects and the trend towards increasing the degree of digital interaction. The composition of the enlarged components of the digitalization level includes: the level of informatization of activities (the use of classical information systems and tools) of construction organizations, the level of digitalization of key management areas (design, construction of facilities, operation, control) of construction organizations and the level of digital interaction of construction organizations within the internal and external environment. The scientific novelty of the methodology lies in the adaptation of classical scientific approaches to the specifics of the construction complex with the simultaneous substantiation of the assessment system, which allows not only to establish the general level of digitalization, but also to identify the least digitalized areas, and also to determine at what stage of the transition to a digital model are individual construction organizations.